Metastability, adiabatic shear bands initiation and plastic strain localization in the AMg6 alloy under dynamic loading - Mikhail Sokovikov; Sergey Uvarov; Mikhail Simonov; Vasiliy Chudinov; Oleg Naimark (Fracture and Structural Integrity)
New conception of adiabatic shear bands (ASB) and adiabatic shear failure mechanisms are proposed as special type of critical phenomen, structural-scaling transition, in the ensembles of microshears, governed by the characteristic non-linearity (metastability) of stored (free) energy of solid with mesodefects. Corresponding free energy release kinetics provides experimentally observed ASB induced staging of plastic strain localization and transition to adiabatic shear failure. ASB staging follows to collective properties of microshears ensemble given by the self-similar solutions of evolution equation providing spatial-temporal microshears localization, momentum transfer and damage localization. The criticality of ASB induced plastic strain localization and failure allows us to avoid the discrepancy in the interpretation of ASB effects as thermo-plastic instability in the balance of the stored energy and structural DRX transformation. The microshear ensemble is considered as the second phase and initiation of collective modes provide different staging according to the metastability decomposition and ASB scaling properties following to the self-similar solutions. Self-similar nature of microshears collective modes providing the ASB dynamics is analyzed as the mechanism of steady plastic wave front unversality in shocked materials. The dynamic split Hopkinson pressure bar tests were conducted with AlMg6 alloy combined with in-situ imaging of temperature kinetics by CEDIP Silver 450M high-speed infrared camera with conclusion of the secondary role of thermoplastic instability at the ASB staging. The microstructural study performed by an electron microscopy revealed the correlated behavior of the ensemble of defects, which can be classified as a structural transition and precursor of ASB induced strain localization and failure. The modeling reflecting the links of self-similar solutions in microshear ensembles with relaxation properies and damage localization was applied for the comparative analysis of ASB staging and temperature dynamics given be the infrared imaging